Peran Pelayanan Kesejahteraan Sosial Anak Terlantar di Uptd Kampung Anak Negeri Surabaya - Rama Dani, Cindy Eka Mellania; Hertati, Diana (Jurnal ilmiah Manajemen Publik dan Kebijakan Sosial, 2024)
Social welfare problems in the community result in delays in the implementation of social functions and result in a high number of poor people and an increasing number of people with social welfare problems. The government, in this case, needs to pay attention to and address the problem of Persons with Social Welfare Problems (PMKS). This study uses a qualitative research method with a descriptive approach. This study intends to obtain a comprehensive and in-depth description of the Role of Social Welfare Services for Neglected Children at UPTD Kampung Anak Negeri Surabaya. Data collection is done by means of interviews, observation, and documentation. In this study the data analysis method that will be used according to (Miles, Huberman, and Saldana 2014) where qualitative data analysis is carried out through several stages, namely, data collection (data collection), data condensation (data condensation), data display (data display), as well as drawing conclusions or verification (conclusion: drawing or verifying). The results of the study show that there are four research focuses that have appropriate service roles in the social welfare of neglected children which include a facilitative role, educational role, representational role, and technical role carried out by UPTD Kampung Anak Negeri Surabaya in social welfare services for neglected children.